Ag / TiO2 multistage cylinder array photocatalyst as well as preparation method and application thereof
Through the use of Ag/TiO2 multi-stage columnar array photocatalyst and combined with 3D composite printing technology, the problem of difficult to efficiently remove 4-nitrophenol in water in the prior art is solved, and efficient, environmentally friendly and low-cost catalytic reduction effect is achieved.
Patent Information
- Application Number
- CN202510186753.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-20
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2045-02-20
AI Technical Summary
The prior art is difficult to efficiently remove 4-nitrophenol dissolved in water. The traditional methods have problems such as high energy consumption, high processing cost and low catalytic efficiency.
The photocatalyst was constructed by 3D composite printing technology using Ag/TiO2 multi-stage columnar array photocatalyst, and the synergistic effect of Ag nanoparticles and TiO2 columnar support was used to improve the efficiency of photocatalytic reduction of 4-nitrophenol.
High-efficiency catalytic reduction of high concentrations of 4-nitrophenol was achieved. With the increase of light intensity, the catalytic efficiency was significantly improved, the conversion frequency (TOF value) was as high as 721.06min-1, and in the five recycling cycles, the catalytic conversion rate was as high as 90% or above.
Smart Images

Figure CN119657126A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photocatalytic composite materials and relates to an Ag / TiO2 multi-level column array photocatalyst for efficiently catalyzing and reducing 4-nitrophenol in water, and a preparation method and application thereof. Background Art
[0002] 4-nitrophenol (4-NP), also known as p-nitrophenol, is a toxic industrial byproduct. It has a certain solubility in water and is stable in water. It is difficult to remove by conventional methods, posing a huge threat to the environment. In particular, when 4-nitrophenol enters the water body, it will sink to the bottom of the water due to its density greater than that of water, and continue to cause water pollution. Traditional methods for removing 4-NP include physical methods, chemical methods, biological methods and photocatalytic degradation methods. Among them, physical methods such as grid filtration and regulating tank homogenization are mainly used to remove impurities such as suspended matter and sediment in wastewater. They can be used to remove 4-NP attached to suspended matter and sediment, but they are not effective in removing 4-NP dissolved in water. Chemical methods generally use oxidants (such as hydrogen peroxide, potassium permanganate, etc.) to oxidize wastewater and decompose 4-NP in water into small molecules, but secondary pollution may occur during the treatment process and the treatment cost is high. The biological treatment method is to use the metabolism of microorganisms to further decompose the organic matter in the wastewater into carbon dioxide and water, avoiding the problem of secondary pollution as much as possible. However, the degradation efficiency of microorganisms for 4-NP is low, and the treatment cycle is long. Photocatalytic reduction is a method that uses light energy to excite catalysts to produce active free radicals, thereby reducing organic pollutants. At present, photocatalytic reduction is considered to be a promising treatment method due to its low energy consumption. However, the lack of efficient photocatalysts suitable for catalytic reduction of 4-NP limits the practical application of photocatalytic reduction in the treatment of 4-NP.
[0003] At present, semiconductor materials have become one of the common photocatalysts because they can generate photogenerated carriers under light excitation. Titanium dioxide (TiO2) is a semiconductor with a relatively narrow band gap and good ultraviolet spectral response. It is a relatively common photocatalyst for 4-NP reduction. Currently, nano-titanium dioxide prepared by the method of dissolving and hydrolyzing tetrabutyl titanate alcohol is commonly used. This nano-titanium dioxide has the advantages of large specific surface area and high photocatalytic activity, but it is usually used as a photocatalyst in a powder structure, which has serious agglomeration phenomenon, which may make it difficult to recover the nanoparticles in the dispersed system. In addition, a single TiO2 semiconductor material can only use ultraviolet light with a shorter wavelength in sunlight, and the utilization rate of solar energy is low, resulting in low efficiency in photocatalytic reduction of 4-nitrophenol. A common solution is to form a plasmon nanoparticle / semiconductor composite material by loading plasmon metal nanoparticles to broaden the light absorption range of the composite material, and use the metal nanoparticles as the photogenerated electron conduction center to slow down the recombination of semiconductor photogenerated electron-hole pairs. At present, the most widely used plasmonic metal nanoparticles are mainly gold (Au), silver (Ag), copper (Cu), platinum (Pt), palladium (Pd) and other materials. Although these metal nanoparticles can show obvious surface plasmon resonance effect, not all plasmonic metal nanoparticles are suitable as photocatalysts for photocatalytic reduction of 4-NP. For example, Pd / TiO2 composite materials show good catalytic efficiency in photocatalytic reduction of 4-NP, but because the surface plasmon resonance effect of Pd nanoparticles is not as significant as that of Au and Ag nanoparticles, the catalytic efficiency of Pd / TiO2 composite photocatalysts is still limited. Summary of the invention
[0004] The purpose of the present invention is to provide an Ag / TiO2 multi-level column array photocatalyst for the efficient catalytic reduction of 4-nitrophenol in water, and a preparation method and application thereof. The Ag / TiO2 multi-level column array photocatalyst described in the present invention can be used for the catalytic reduction of 4-nitrophenol in water, and has the advantages of good photocatalytic effect, recyclability, and enhanced photocatalytic effect with the increase of light intensity.
[0005] The technical solution provided by the present invention is as follows:
[0006] The preparation method of Ag / TiO2 multi-level column array photocatalyst comprises the following steps:
[0007] TiO2 powder is mixed with polyethylene glycol-polypropylene glycol copolymer, and a TiO2 array is vertically printed on an alumina ceramic sheet; the printed TiO2 array is naturally dried and then sintered in a muffle furnace to obtain a TiO2 column array;
[0008] A mixture of diisopropoxy diacetylacetonate titanium and n-butanol is spin-coated on the surface of the TiO2 column array, and then dried, heated and cooled to room temperature, and then placed in a mixed aqueous solution of tetrabutyl titanate and hydrochloric acid for a first hydrothermal reaction, and then dried, heated and annealed to obtain a TiO2 multi-level column array with TiO2 nanorods grown thereon;
[0009] The TiO2 multilevel column array on which TiO2 nanorods were grown was modified by immersing it in an ethanol solution of 3-(triethoxysilyl)propylsuccinic anhydride, and then rinsed and placed in a silver nitrate aqueous solution for a second hydrothermal reaction to obtain an Ag / TiO2 multilevel column array photocatalyst.
[0010] Furthermore, the TiO2 powder includes TiO2 powder with a particle size of 20-30 nm and TiO2 powder with a particle size of 180-220 nm, and the mass ratio of the TiO2 powder with a particle size of 20-30 nm to the TiO2 powder with a particle size of 180-220 nm is 1:3-5.
[0011] Furthermore, the sintering temperature is 800-1000° C., the sintering time is 3-5 hours, and the heating rate is 4-6° C. / min.
[0012] Furthermore, the temperature of the first hydrothermal reaction is 150-170°C, and the reaction time is 40-80 min.
[0013] Furthermore, the temperature of the second hydrothermal reaction is 80-120° C., and the reaction time is 16-20 h.
[0014] Furthermore, the volume ratio of diisopropoxy titanium bisacetylacetonate to n-butanol is 3-4:6-7.
[0015] The present invention also provides a Ag / TiO2 multi-level column array photocatalyst, which is prepared by the above-mentioned preparation method.
[0016] The present invention also provides the use of the Ag / TiO2 multi-level column array photocatalyst in treating organic wastewater pollution.
[0017] The present invention also provides the use of the Ag / TiO2 multi-level column array photocatalyst in treating 4-NP pollution in organic wastewater.
[0018] Furthermore, the photocatalytic light intensity is greater than 50 mW / cm 2 .
[0019] Furthermore, the concentration of the 4-NP is greater than 10 mM.
[0020] Beneficial Effects
[0021] Ag nanoparticles not only have a significant surface plasmon resonance effect, but also have a good effect on the photocatalytic reduction of 4-NP. Therefore, loading Ag nanoparticles on a TiO2 columnar bulk carrier to develop a recyclable Ag / TiO2 multi-level columnar photocatalyst is of great significance for the efficient, environmentally friendly, and low-cost removal of 4-NP from sewage. The present invention constructs an Ag / TiO2 multi-level columnar array photocatalyst through 3D composite printing technology, and achieves efficient catalytic reduction of high-concentration (14.38 mM) 4-NP under light conditions; with the increase of light intensity, the performance of Ag / TiO2 catalysis of 4NP is significantly improved, and is positively correlated with the light intensity. Under 2.5 suns, the photocatalytic reaction time of reducing 4-NP with sodium borohydride as a hydrogen source is less than 2 minutes, and the conversion frequency (TOF value) of the photocatalyst is as high as 721.06 minutes -1 , which is about 46.7 times higher than the dark reaction. Ag and TiO2 carrier composites have obvious synergistic effects; the Ag / TiO2 synergistic effect increases with the increase of light intensity and is positively correlated with the light intensity. The catalytic conversion rate of Ag / TiO2 multi-level column array photocatalyst is as high as 90% or more in 5 recycling cycles. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Schematic diagram of the preparation process of the method of the present invention;
[0023] Figure 2 This is an optical photograph of the Ag / TiO2 multi-level pillar array photocatalyst;
[0024] Figure 3 The SEM images of TiO2 nanorods grown on TiO2 cylinders and the SEM images of Ag nanoparticles loaded on TiO2 nanorods;
[0025] Figure 4 High-resolution images taken by HRTEM of Ag NPs successfully loaded on TiO2 nanorods and distribution images of each element;
[0026] Figure 5 To analyze the composition of Ag / TiO2 multi-level pillar array photocatalyst using XRD; and the XPS spectrum of Ag element;
[0027] Figure 6 is the value of 4-NP concentration changing with reaction time in the photocatalytic reduction of 4-NP by Ag / TiO2 multi-level pillar array photocatalyst under dark and 1 sun conditions (C t / C0), its ln value and TOF value.
[0028] Figure 7This is a bar graph showing the conversion rate of 4-NP reduction catalyzed by Ag / TiO2 multi-level column array photocatalyst under 1 sun irradiation conditions and cycles of 1 to 5.
[0029] Figure 8 is the value of 4-NP concentration changing with reaction time in the photocatalytic reduction of 4-NP by Ag / TiO2 multi-level pillar array photocatalyst under different intensities of sunlight irradiation conditions (C t / C0), its ln value and TOF value. DETAILED DESCRIPTION
[0030] The present invention will be described in detail below with reference to the accompanying drawings.
[0031] Example 1
[0032] Figure 1 The present invention provides a flow chart for preparing the Ag / TiO2 multi-level column array photocatalyst. The preparation method of the Ag / TiO2 multi-level column array photocatalyst comprises the following steps:
[0033] S1: Select TiO2 powders with particle sizes of 25 nm and 200 nm, adjust the slurry viscosity together with 10wt% polyethylene glycol-polypropylene glycol copolymer (F127, manufacturer: Sigma-Aldrich, USA, product number: P2443-250g, CAS: 9003-11-6), mix them according to the mass ratio of TiO2 powder and 10wt% F127 of 1:4, select a printing needle with an inner diameter of 0.21 mm, so that it can be vertically printed under an air pressure of 300-550Kpa, and vertically print a 10*10*1.2mm TiO2 array on a 15*15*2 mm alumina ceramic sheet; after the printed TiO2 array is naturally dried, it is sintered in a muffle furnace at 900℃ in air for 4h, with a heating rate of 5℃ / min to obtain a TiO2 column array.
[0034] S2: Take 3.5 mL of diisopropoxy diacetylacetonate titanium and 6.5 mL of n-butanol into a beaker, stir vigorously with a magnetic stirrer for 4 h to mix them evenly, and obtain TiO2 sol as a spin coating liquid. Then, fix the TiO2 column array in a spin coater, drip an appropriate amount of TiO2 sol about 200 μL on the surface of the array, and spin coat it at a speed of 5000 rpm for 30 s, then place it on a heating plate, dry it at 100℃ for 10 min, and adjust the heating plate to 400℃, keep the spin-coated TiO2 multi-level column array at 400℃ for 1h, and then naturally cool it to room temperature in an air atmosphere to obtain a TiO2 column array with a layer of TiO2 film attached to the surface;
[0035] S3: Add 5mL of deionized water and 5mL of concentrated hydrochloric acid (12 mM) and 0.4mL of tetrabutyl titanate into a 25mL hydrothermal reactor, then place the TiO2 column array with a layer of TiO2 film attached to the surface into the reactor, and carry out the first hydrothermal reaction at 160℃ for 1h. After the first hydrothermal reaction is completed, wash it with ethanol and water alternately for 5 times, dry it in an oven at 50℃ for half an hour, and then heat it to 450℃ in a muffle furnace with a heating rate of 5℃ / min, and keep it at 450℃ for 2h. Then cool it down to room temperature naturally in the muffle furnace to realize the growth of TiO2 nanorods on the TiO2 column array, and obtain a TiO2 multi-level column array with TiO2 nanorods grown on it.
[0036] S4: The TiO2 multilevel column array with TiO2 nanorods grown on it was modified by immersing it in 2 mL of 0.1wt% 3-(triethoxysilyl)propyl succinic anhydride ethanol solution. The sample was sealed and placed at room temperature for 8 h, and then rinsed with ethanol and deionized water for 3-5 times in sequence to obtain a TiO2 multilevel column array with 3-(triethoxysilyl)propyl succinic anhydride modified on the surface.
[0037] S5: 4 mL of 0.15 g / L silver nitrate aqueous solution was added to a 25 mL hydrothermal reactor as a precursor, and the TiO2 multilevel column array modified with 3-(triethoxysilyl)propyl succinic anhydride on the surface was placed in the reactor for a second hydrothermal reaction. The reaction temperature was 100 °C and the reaction time was 18 h. Ag / TiO2 multilevel column array photocatalyst loaded with Ag nanoparticles was obtained. Its optical photograph is shown in FIG. Figure 2 shown.
[0038] The Ag / TiO2 multilevel pillar array photocatalyst was characterized by scanning electron microscopy (SEM). Figure 3 As shown, the size of TiO2 nanorods is about 100~200nm*1µm; Ag nanoparticles are successfully loaded on the TiO2 nanorods and are evenly distributed.
[0039] The Ag / TiO2 multilevel pillar array photocatalyst was characterized by high-resolution transmission electron microscopy (HRTEM). Figure 4 As shown in Figure 2, the lattice spacing of Ag NPs is about 0.233 nm, which matches the (111) crystal plane of Ag nanocrystals. In addition, EDS element mapping obtained by HRTEM shows that a large number of Ag NPs are loaded on the TiO2 nanorods.
[0040] The composition of Ag / TiO2 multilevel pillar array photocatalyst was analyzed by X-ray diffractometer (XRD) and X-ray photoelectron spectroscopy (XPS). Figure 5As shown in the figure, the XRD spectrum shows that the TiO2 in the Ag / TiO2 multi-level column array photocatalyst is mainly anatase phase. At the same time, the characteristic peaks of the Ag element were detected in the XRD spectrum. Combined with the XPS spectrum, it shows that the 3d orbital of Ag has two characteristic peaks, 3d 3 / 2 The binding energy value of the characteristic peak corresponding to the orbital is 374.1 eV, 3d 5 / 2 The binding energy of the characteristic peak of the orbital is 368.1 eV. Compared with the binding energy of 374.2 eV corresponding to the standard characteristic peak of the 3d orbital of the Ag element (3d 3 / 2 ) and 368.2 eV (3d 5 / 2 ), the characteristic peaks of Ag element in Ag / TiO2 samples all shifted negatively. Therefore, it can be inferred that there is also a Schottky heterojunction between Ag and TiO2 and electron transfer occurs. In the Ti 2p spectrum, the two peaks at 464.5 and 458.7 eV are respectively attributed to Ti in TiO2. 4+ Ti 2p 1 / 2 and Ti 2p 3 / 2 .
[0041] Example 2
[0042] The reaction steps of Ag / TiO2 multi-level column array photocatalyst catalytic reduction of 4-NP in water are as follows:
[0043] A 14.38 mM 4-NP aqueous solution (14.38 mM is the highest concentration of 4-NP reported so far for photocatalytic reduction) was prepared as a reactant, and 4 mL of 4-NP solution was taken as a single reaction solution in each experiment. Before the experiment, 0.4 g of sodium borohydride (NaBH4) powder was weighed and added to the 4-NP solution, and stirred continuously to dissolve it quickly. When the NaBH4 powder was completely dissolved, 80 μL of the reaction solution was taken and diluted 50 times with deionized water. The absorption spectrum of the reaction solution was measured by a UV-visible spectrophotometer and the absorbance C0 of the solution at λ = 400 nm was recorded. Then, the Ag / TiO2 multilevel column array photocatalyst was placed in the mixed solution and tested under dark conditions and 1 sunlight (100 mW / cm 2 ) Under illumination conditions, at 0.5 min, 1 min, 2 min, 3 min, 5 min, 7 min, 12 min, and 17 min of reaction, 80 μL of the reaction solution was drawn each time, diluted 50 times with deionized water, and its absorption spectrum was measured and the absorbance C of the solution at λ = 400 nm was recorded. t The concentration change of 4-NP in the solution is characterized by the change of absorbance. In the experiment, all catalytic reduction reactions were carried out at room temperature and no stirring was required during the reaction.
[0044] Performance evaluation criteria: turnover frequency (TOF), i.e., the catalytic efficiency of the catalytic reduction reaction of 4-NP. Generally speaking, TOF is an important parameter for evaluating the catalytic performance of metal-based heterogeneous catalysts, and the TOF value is positively correlated with the catalytic activity of the catalyst. In this embodiment, TOF refers to the number of catalytic cycles per unit time, i.e., the molar amount of 4-NP reduced per mole of Ag nanoparticles per minute.
[0045] Figure 6 is the value of the change of 4-NP concentration with reaction time in the photocatalytic reduction of 4-NP by Ag / TiO2 multi-level pillar array photocatalyst under light and dark conditions (C t / C0), its ln value and TOF value. The TOF value of Ag / TiO2 multi-level column array photocatalyst catalytic reduction of 4-NP under one sunlight irradiation reached 168.66min -1 , compared with the TOF value in dark conditions, it is increased by 1092%.
[0046] Example 3
[0047] The test steps of Ag / TiO2 multi-level column array photocatalyst catalytic reduction of 4-NP in water are as follows:
[0048] Take 4 mL of 14.38 mM (C0) 4-NP aqueous solution as the reactant, add 0.4 g NaBH4 powder to it, and stir continuously to dissolve it quickly. When the NaBH4 powder is completely dissolved, take 80 μL of the reaction solution and dilute it 50 times with deionized water. The absorption spectrum of the reaction solution is measured by UV-visible spectrophotometer and the absorbance of the solution at λ = 400 nm is recorded. Then, the Ag / TiO2 multi-level column array photocatalyst is placed in the mixed solution. Under the condition of 1 sun light illumination, take 80 μL of the reaction solution at 2 minutes of reaction, dilute it 50 times with deionized water, measure its absorption spectrum and record the absorbance of the solution at λ = 400 nm. The concentration of 4-NP in the solution is characterized by the change in absorbance (C t ) changes to C t / C0 as the conversion rate of catalytic reduction of 4-NP. After the reaction was completed, the Ag / TiO2 multi-level column array photocatalyst was taken out, rinsed with ethanol and water for 3-5 times, and heated at 400 o Place the sample on a heating plate for 60 minutes to dry. Repeat the above reaction test operation for 4 times and record the C value of the total 5 cycle tests. t / C0 value, such as Figure 7 As shown, the results show that the catalytic conversion rate of the Ag / TiO2 multi-level pillar array photocatalyst is as high as over 90% in 5 recycling cycles.
[0049] Example 4
[0050] Ag / TiO2 multi-level pillar array photocatalyst, and three other catalysts, namely TiO2 multi-level pillar array photocatalyst, Ag / TiO2 pillar array photocatalyst and Pd / TiO2 multi-level pillar array photocatalyst, were provided for comparative experiments.
[0051] The preparation process of Ag / TiO2 multi-level pillar array photocatalyst is prepared according to S1-S5 in Example 1.
[0052] The preparation process of the TiO2 multi-level column array photocatalyst is prepared according to S1-S4 in Example 1.
[0053] Preparation process of Ag / TiO2 column array photocatalyst: According to S1 in Example 1, a TiO2 column array is prepared, and the TiO2 multi-level column array is immersed in 2 mL of 0.1wt% 3-(triethoxysilyl)propyl succinic anhydride ethanol solution. Then, it is sealed and placed at room temperature for 8 h, and the sample is rinsed 3-5 times with ethanol and deionized water in sequence to obtain a TiO2 column array with surface modified with 3-(triethoxysilyl)propyl succinic anhydride. Subsequently, 4 mL of 0.15 g / L silver nitrate aqueous solution is added as a precursor in a 25 mL hydrothermal reactor, and the TiO2 column array with surface modified with 3-(triethoxysilyl)propyl succinic anhydride is placed in a reactor for hydrothermal reaction, the reaction temperature is 100 ° C, and the reaction time is 18 h, and an Ag / TiO2 column array photocatalyst loaded with Ag nanoparticles is obtained.
[0054] The preparation process of Pd / TiO2 multi-level column array photocatalyst is as follows S1-S4 in Example 1 to prepare a TiO2 multi-level column array with surface modified with 3-(triethoxysilyl)propyl succinic anhydride, and then 4 mL of 0.15 g / L palladium chloride (PdCl2) aqueous solution is added as a precursor to a 25 mL hydrothermal reactor, and the TiO2 column array with surface modified with 3-(triethoxysilyl)propyl succinic anhydride is placed in the reactor for hydrothermal reaction at a reaction temperature of 100°C and a reaction time of 18 h to obtain a Pd / TiO2 multi-level column array photocatalyst loaded with Pd nanoparticles.
[0055] Take 4 portions of 4 mL of 14.38 mM (C0) 4-NP aqueous solution as the reactant, add 0.4 g of NaBH4 powder to each, and stir continuously to dissolve it quickly. When the NaBH4 powder is completely dissolved, take 80 μL of the reaction solution and dilute it 50 times with deionized water. The absorption spectrum of the reaction solution is measured by UV-visible spectrophotometer and the absorbance of the solution at λ = 400 nm is recorded. Then, the Ag / TiO2 multilevel pillar array photocatalyst, the TiO2 multilevel pillar array photocatalyst, the Ag / TiO2 pillar array photocatalyst and the Pd / TiO2 multilevel pillar array photocatalyst were placed in 4 portions of 4 mL of the mixed solution, respectively, and 80 μL of the reaction solution was taken each time at 0.5 min, 1 min, 2 min, 3 min, 5 min, 7 min, 12 min, and 17 min under dark conditions and 1 sun illumination conditions, and diluted 50 times with deionized water, and the absorption spectrum was measured and the absorbance C of the solution at λ = 400 nm was recorded. t The concentration change of 4-NP in the solution is characterized by the change of absorbance. In the experiment, all catalytic reduction reactions were carried out at room temperature and no stirring was required during the reaction. The specific experimental conditions and catalytic effects are shown in Table 1.
[0056] Table 1:
[0057]
[0058] The results showed that only the Ag / TiO2 multi-level pillar array photocatalyst achieved a photocatalytic reduction reaction time of 4-NP (conversion rate of 90%) of less than 2 minutes under 1 sun irradiation. The TiO2 multi-level pillar array photocatalyst did not achieve 90% conversion of 4-NP within 2 hours, whether in the dark or under light conditions, indicating that Ag nanoparticles play a key role in the photocatalytic reduction of 4-NP.
[0059] Example 5
[0060] Light intensity dependence experiment
[0061] In order to further confirm the high catalytic activity of Ag / TiO2 multi-level pillar array photocatalyst under high light intensity, catalytic experiments under different light intensities were carried out according to the catalytic reduction reaction steps of 4-NP in water in Example 2. The results are shown in Figure 2. Figure 8 As shown in the figure, as the light intensity increases, the photocatalytic efficiency of the Ag / TiO2 multi-level column array photocatalyst increases with the increase of light intensity and is positively correlated with the light intensity. Under 2.5 suns, the TOF value is as high as 721.06min -1 , breaking through the limitation that the efficiency of traditional semiconductor-based catalysts is negatively correlated with light intensity.
Claims
1. A method for preparing a Ag / TiO2 multi-level column array photocatalyst, characterized in that: The following steps are involved: TiO2 powder is mixed with polyethylene glycol-polypropylene glycol copolymer, and a TiO2 array is vertically printed on an alumina ceramic sheet; the printed TiO2 array is naturally dried and then sintered in a muffle furnace to obtain a TiO2 column array; A mixture of diisopropoxy diacetylacetonate titanium and n-butanol is spin-coated on the surface of the TiO2 column array, and then dried, heated and cooled to room temperature, and then placed in a mixed aqueous solution of tetrabutyl titanate and hydrochloric acid for a first hydrothermal reaction, and then dried, heated and annealed to obtain a TiO2 multi-level column array with TiO2 nanorods grown thereon; The TiO2 multilevel column array on which TiO2 nanorods were grown was modified by immersing it in an ethanol solution of 3-(triethoxysilyl)propylsuccinic anhydride, and then rinsed and placed in a silver nitrate aqueous solution for a second hydrothermal reaction to obtain an Ag / TiO2 multilevel column array photocatalyst.
2. The method for preparing the Ag / TiO2 multi-level column array photocatalyst according to claim 1, characterized in that: The TiO2 powder includes TiO2 powder with a particle size of 20-30 nm and TiO2 powder with a particle size of 180-220 nm, and the mass ratio of the TiO2 powder with a particle size of 20-30 nm to the TiO2 powder with a particle size of 180-220 nm is 1:3-5.
3. The method for preparing the Ag / TiO2 multi-level column array photocatalyst according to claim 1, characterized in that: The sintering temperature is 800-1000° C., the sintering time is 3-5 hours, and the heating rate is 4-6° C. / min.
4. The method for preparing the Ag / TiO2 multi-level column array photocatalyst according to claim 1, characterized in that: The volume ratio of diisopropoxy diacetylacetonate titanium to n-butanol is 3-4:6-7.
5. The method for preparing the Ag / TiO2 multi-level column array photocatalyst according to claim 1, characterized in that: The temperature of the first hydrothermal reaction is 150~170℃, and the reaction time is 40~80min.
6. The method for preparing the Ag / TiO2 multi-level column array photocatalyst according to claim 1, characterized in that: The temperature of the second hydrothermal reaction is 80~120℃, and the reaction time is 16~20h.
7. An Ag / TiO2 multi-level column array photocatalyst, characterized in that: Prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the Ag / TiO2 multi-level column array photocatalyst as claimed in claim 7 in treating organic wastewater pollution.
9. Use of the Ag / TiO2 multi-level column array photocatalyst according to claim 7 in the photocatalytic reduction of 4-nitrophenol in water.
10. The use according to claim 9, characterized in that: The photocatalytic light intensity is greater than 50mW / cm 2 .
Citation Information
Patent Citations
Synthesis method of TiO2 porous framework / Pd nanoparticle composite catalyst, composite catalyst and application of composite catalyst
CN110871068A
Preparation method of photo-composite catalyst, photo-composite catalyst and application of photo-composite catalyst
CN111569870A
Precious metal modified titanium dioxide nanorod array with excellent surface enhanced Raman scattering property and preparation method and application of precious metal modified titanium dioxide nanorod array
CN113267483A